Evaluation of the ICD-10 system in coding revascularisation procedures in patients with peripheral arterial disease in England: a retrospective cohort study using national administrative and clinical databases. (January 2023) - Birmpili, Panagiota; Atkins, Eleanor; Li, Qiuju; Johal, Amundeep S.; Waton, Sam; Williams, Robin; Pherwani, Arun D.; Cromwell, David A.
Summary: Background: Many studies evaluating care in hospitals in England use the Hospital Episode Statistics (HES) administrative database. The aim of this study was to explore whether the International Classification of Diseases 10th Revision (ICD-10) system used by HES supported the evaluation of care received by patients with peripheral arterial disease (PAD) who had revascularisation. Methods: This retrospective cohort study used records on patients who had revascularisation for PAD between 1st January 2017 and 31st December 2019 in England, collected prospectively in the National Vascular Registry (NVR) and linked to HES. Patients were excluded if their NVR record did not have a match in HES, due to lack of consent or different admission and procedure dates. Agreement between different presentations of PAD recorded in the NVR and the ICD-10 diagnostic codes recorded in HES was evaluated using the unweighted Kappa statistic and sensitivity and specificity. Agreement between the NVR and HES was also assessed for gender, age, comorbidities, mode of admission, and procedure type and side. Findings: In total, 20, 603 patients who had 24, 621 admissions were included in the study. Agreement between NVR and HES on patient gender (Kappa = 0.98), age (Kappa = 0.98), mode of admission (Kappa = 0.80), and procedure type and side (Kappa = 0.92 and 0.87, respectively) was excellent. When all diagnostic fields in HES were explored, substantial agreement was observed for chronic ischaemia with tissue loss (Kappa = 0.63), but it was lower for chronic ischaemia without tissue loss (Kappa = 0.32) and acute limb ischaemia (Kappa = 0.15). Agreement on comorbidities was mixed; excellent for diabetes (Kappa = 0.82), moderate for chronic lung disease (Kappa = 0.56), chronic kidney disease (Kappa = 0.56), and ischaemic heart disease (Kappa = 0.45) and fair for chronic heart failure (Kappa = 0.35). Interpretation: The diagnostic ICD-10 codes currently used in HES cannot accurately differentiate between stages of PAD. Therefore, studies using HES to examine patterns of care and outcomes for patients with PAD are likely to suffer from misclassification bias. Adopting an extended ICD-10 system or the ICD-11 version released to the World Health Organisation member states in 2022, may overcome this problem. Funding: Healthcare Quality Improvement Partnership (HQIP ).